2013
DOI: 10.1063/1.4791763
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the colossal dielectric properties in double-perovskite Sr2CoNbO6

Abstract: Sr2CoNbO6 ceramics were prepared via the solid-state reaction route. The dielectric properties of Sr2CoNbO6 ceramics were investigated as a function of temperature (90–330 K) in the frequency range from 20 Hz to 10 MHz. Our results reveal that the dielectric properties of Sr2CoNbO6 are closely linked with the conductivity of the sample. The conductivity is dominated by hopping localized carriers. The hopping process not only produces considerable conductivity followed the universal dielectric response behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The Y 2 FeCoO 6 has a higher value of ε r comparative to many other double perovskites such as La 2 FeCoO 6 , Sr 2 CoNbO 6 , Pr 2 CoTiO 6 , Po 2 CoZrO 6 , La 2 NiMnO 6 at room temperature, which makes it a useful material for electrochemical application. [ 8,9,11,39,40 ] The value of tan δ for Y 2 FeCoO 6 is almost similar to other double perovskites in high‐frequency range >1 kHz. However, this material has a large tangent loss in the low‐frequency and high‐temperature range in comparison to other similar compounds.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The Y 2 FeCoO 6 has a higher value of ε r comparative to many other double perovskites such as La 2 FeCoO 6 , Sr 2 CoNbO 6 , Pr 2 CoTiO 6 , Po 2 CoZrO 6 , La 2 NiMnO 6 at room temperature, which makes it a useful material for electrochemical application. [ 8,9,11,39,40 ] The value of tan δ for Y 2 FeCoO 6 is almost similar to other double perovskites in high‐frequency range >1 kHz. However, this material has a large tangent loss in the low‐frequency and high‐temperature range in comparison to other similar compounds.…”
Section: Resultssupporting
confidence: 63%
“…[ 3–7 ] Furthermore, the room temperature giant relative permittivity and low loss factor of such materials, viz., Ba 2 PrRuO 6 , La 2 MnCoO 6 , La 2 FeCoO 6 , Sr 2 CoNbO 6 , Ho 2 CdTiO 6 , Pr 2 CoTiO 6 , Y 2 CoMnO 6 make them very useful for energy storage application. [ 6,8–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the Sr 2 CoNbO 6 and related compounds crystalize in cubic phase with the random occupancy of B-site cations i.e. perovskite unit cell with P m 3m space group [34,39,62], while others have shown the rhombohedral structure with R 3m space group [33] as well as octahedral tilted tetragonal structure with I4/m space group having a 0 a 0 c − Glazer notation i.e antiphase tilting of NbO 6 and CoO 6 octahedra along [001] direction [36][37][38]63]. It is well known that perovskites with ideal cubic structure (P m 3m with the random occupancy of B-site cations) is centrosymmetric and hence Raman inactive, while group theory predict four Raman active modes for cubic B-site ordered structure (F m 3m double perovskite structure, where unit cell doubles in all the three crystallographic directions) i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The density functional theory (DFT) calculations within the generalized gradient approximation predict the semiconducting nature of the material with 0.2 eV band gap [38], which is supported by the positive temperature coefficient of conductivity carried out on bulk Sr 2 CoNbO 6 with an activation energy of 0.25-0.35 eV, where conductivity sensitively increase with the oxygen partial pressure at 973 K [35,40]. Wang et al showed the colossal dielectric properties in the compound, where the dielectric response was found to be closely related to the conduction mechanism governed by the hopping of localized charge carriers [36]. Electronic band structure can give a valuable information about the spin state of Co 3+ and hence the magnetic properties of Sr 2 CoNbO 6 as LS Co 3+ is insulating while IS/HS states are electrically conducting due to the presence of unpaired electrons.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation